Bahasa Inggris - Ridwan, Zainal Muttaqin; Fahriansah; Mutia Sumarni; Di Ami Fitri (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2022)
Purpose – The purpose of this research is knowing the level of effectiveness and implementation of the productive infaq distribution program in improving the mustahik economy. Method – This research uses descriptive qualitative research, is a research that describes the state of the object of research at the present time as it is based on the results of observations, interviews, and documentation. Result – The results showed that the distribution of productive infaq has been effective, it can be seen from the increase in the income of mustahik after receiving productive infaq from Baitul Mal Aceh Tamiang. The results also show that the distribution of productive infaq aims to help the poor who have small and medium businesses to provide capital injections to suppress the movement of moneylenders and increase family income. Limitation – This research has limitations in terms of the relatively small number of research subjects, then the research subjects are mustahik from the Baitul Mal Aceh Tamiang food security program which will be distributed productive infaq to mustahik who are entitled to receive it. Practical Implication – As a practical implication, the results of this study can be used as a reference by the government, especially zakat institutions in distributing productive infaq to improve the mustahik economy. So that by maintaining all existing SOPs, it provides an optimal impact in the distribution process of all kinds of activities.